1994
DOI: 10.1002/hon.2900120104
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in low grade non‐Hodgkin's lymphoma: relevance of the number of sites involved, absolute lymphocyte count and serum immunoglobulin level

Abstract: Eighty-eight patients with low grade non-Hodgkin's lymphoma were followed for a median period of 63 months. Sixty-eight per cent of the group were centrocytic/centroblastic B cell lymphomas by the updated Kiel classification. Fifty-one (58 per cent) of the patients were stage IV by the Ann Arbor classification. In 18 of these patients the bone marrow was the only site of extranodal involvement. Univariate survival analysis showed that the sum of involved sites was more discriminatory than Ann Arbor stage. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…12 Low levels of one type or more of immunoglobulin were frequently found in this study. The suppression of immunoglobulin was mild, this finding has repeatedly been reported by other workers 13 and has been associated with advanced disease . This immunosuppression is related to decreased Ig production resulting from B-cell depletion due to the replacement of lymphoid tissue or due to the effect of treatment 14,15 or as a result of malnutrition.…”
Section: Frequency Of M Bands Showed By Serum Protein Electrophoresissupporting
confidence: 85%
“…12 Low levels of one type or more of immunoglobulin were frequently found in this study. The suppression of immunoglobulin was mild, this finding has repeatedly been reported by other workers 13 and has been associated with advanced disease . This immunosuppression is related to decreased Ig production resulting from B-cell depletion due to the replacement of lymphoid tissue or due to the effect of treatment 14,15 or as a result of malnutrition.…”
Section: Frequency Of M Bands Showed By Serum Protein Electrophoresissupporting
confidence: 85%
“…However, they looked at a heterogenous histological group of NHL patients. Parker et al (1994) reported shortened survival in patients with an ALC <1 × 10 9 /l at diagnosis in a small heterogenous group of NHL patients, including follicular, mixed small and large cleaved and large cell, diffuse large cell, small lymphocytic lymphoma and mycosis fungoides. In contrast to the FLIPI study, where the ALC was not included in the top five prognostic factors used by the clinical committee of the FLIPI project in order to make its use easier in routine practice, our study differed as follows: (i) we included only grades 1 and 2 FLs, as grade 3 FLs tend to behave similarly to diffuse large cell lymphoma; and (ii) we identified that an ALC ≥ 1 × 10 9 /l was an independent prognostic factor regardless of whether the patient was initially observed or treated, whereas treatment was not included in the prognostic analysis of the FLIPI study.…”
Section: Discussionmentioning
confidence: 94%
“…IL1RN , along with IL1A and IL1B , make up the interleukin 1 ( IL1) gene family cluster on chromosome 2q. Specifically, IL1RN is known to alter IL1B expression levels (Santtila et al , 1998), leading to a modulation of a variety of IL1 ‐related immune and inflammatory responses, which may affect the risk of haematopoietic cancers (Parker et al , 1994; Bastion et al , 1997; Elahi et al , 2005). Further, variants in IL1 genes have been associated with susceptibility to and clearance of infectious agents (Witkin et al , 2002).…”
Section: Discussionmentioning
confidence: 99%